Detection of Catechol using a Biosensor Based on Biosynthesized Silver nanoparticles and Polyphenol Oxidase Enzymes - Sandeep,S. (2019)
In the present work, we report the development of a polyphenol oxidase (PPO) sensor for the selective and sensitive detection of catechol, using biosynthesized silver nanoparticles (AgNPs). For the sensor development, AgNPs biosynthesized using the leaf extract of Convolvulus pluricaulis, were successfully deposited onto a polypyrrole modified graphite electrode (Gr/PPy). The resulting Gr/PPy/AgNPs electrode was further used as a matrix for the immobilization of the PPO enzyme extracted from Manilkara Zapota (sapota). The morphological characteristics of the developed Gr/PPy/AgNPs/PPO sensor were studied using a scanning electron microscope (SEM). The sensor performance was evaluated and optimized using cyclic voltammetry (CV), differential pulse voltammetry (DPV), chrono amperometry (CA) and electrochemical impedance spectroscopy (EIS) methods. Under neutral pH conditions, the developed sensor showed excellent electro catalytic activity towards catechol detection. The sensor performed well in the concentration range of 0.001 to 0.015 mM, with the detection limit of 0.47 µM, and sensitivity of 13.66 µM-1cm-2. The biosensor response was found to be uninfluenced by some common interferents, and it also showed good storage stability and repeatability. The practical applicability of the PPO biosensor for catechol detection in real samples was assessed by examining the catechol content in a green tea sample. The sensor could detect catechol content in a green tea sample, to an accuracy of about 98%, thereby establishing its efficiency in real sample analysis.